2023
DOI: 10.1002/cam4.5874
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of endoplasmic reticulum stress in colorectal cancer for predicting prognosis and developing treatment options

Abstract: Background An increasing body of evidence supports an essential role for endoplasmic reticulum stress (ERS) in colorectal cancer (CRC). In this study, we developed an ERS‐related genes (ERSRGs) model to aid in the prognostic evaluation and treatment of CRC patients. Methods The training set and validation set data were extracted from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO), respectively. ERSRGs were obtained from the GeneCards database. A prognostic risk scoring model was constructed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Expression of XBP1s promotes the proliferation of colon cancer cells (Liu et al 2023 ). In a risk model of ER stress-related genes (ERSRGs) for prognostic assessment and treatment of CRC patients, the high-risk group was shown to be more resistant to the chemotherapeutic agent 5-Fluorouracil (5-FU), and risk scores were positively correlated with 5-FU resistance(Geng et al 2023 ). ATF6 expression is detected in colorectal cancer but is absent in normal colonic mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of XBP1s promotes the proliferation of colon cancer cells (Liu et al 2023 ). In a risk model of ER stress-related genes (ERSRGs) for prognostic assessment and treatment of CRC patients, the high-risk group was shown to be more resistant to the chemotherapeutic agent 5-Fluorouracil (5-FU), and risk scores were positively correlated with 5-FU resistance(Geng et al 2023 ). ATF6 expression is detected in colorectal cancer but is absent in normal colonic mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cell cycle arrest depends on the activation of DNA damage signaling pathways, which also influence the proliferation of cancer cells ( 5 ). Previous studies have reported that selectively targeting specific biomarkers involved in the regulation of cell division or apoptosis can have a significant impact on tumor growth or the supportive environment of cancer cells, while having minimal influence on normal cells ( 6 8 ). The identification of compounds that can inhibit the cell cycle and induce apoptosis shows promise in the development of potential drugs for CRC therapy.…”
Section: Introductionmentioning
confidence: 99%